Ritual practices in a hospital program. An approach from social anthropology (La Rivada, 2024)
Rituals are a classic topic in Social Anthropology. In this paper I recover some conceptual formulations about ritual processes for the analysis of a set of practices that allows to delimit a specific moment in the therapeutic journey of the patients of the Multidisciplinary Programme for the Treatment of Obesity, implemented in the province of Misiones. Here, I propose conceptualizing the experience of going through the admission office as a rite of passage, as it allows a change in status for people/individuals seeking treatment for obesity. The aim is to reflect on the symbol and meanings at play in context of hospital care. An ethnographic approach to this universe led me to carry out field work (May 2019 - May 2023) at a hospital, where I was able to document events that occurred within the framework of the “Open Talks” and in the medical consultations carried out in the aforementioned program. As a result, I argue that patient care in the admission office and in the open talks spaces constitute a rite of passage for people who attend seeking treatment for this condition. Through medical diagnosis and the symbolic dimension associated with it, people undergo a transformation: from percieving themselves as healthy to viewing themselves as ill. In this context, the ritual acquires a fundamental role due to its symbolism and profound social meaning.
Keywords: ritual; body; obesity; disease; MeSH